Bacillus anthracis Peptidoglycan Integrity Is Disrupted by the Chemokine CXCL10 through the FtsE/X Complex - Molly A. Hughes; Katie R. Margulieux; Benjamin K. Liebov; Venkata S. K. K. S. Tirumala; Arpita Singh; John H. Bushweller; Robert K. Nakamoto (Frontiers in Microbiology, 2017)
The antimicrobial activity of the chemokine CXCL10 against vegetative cells of Bacillus anthracis occurs via both bacterial FtsE/X-dependent and-independent pathways. Previous studies established that the FtsE/X-dependent pathway was mediated through interaction of the N-terminal region(s) of CXCL10 with a functional FtsE/X complex, while the FtsE/X-independent pathway was mediated through the C-terminal α-helix of CXCL10. Both pathways result in cell lysis and death of B. anthracis. In other bacterial species, it has been shown that FtsE/X is involved in cellular elongation though activation of complex-associated peptidoglycan hydrolases. Thus, we hypothesized that the CXCL10-mediated killing of vegetative cells of B. anthracis through the FtsE/X-dependent pathway resulted from the disruption of peptidoglycan processing. Immunofluorescence microscopy studies using fluorescent peptidoglycan probes revealed that incubation of B. anthracis Sterne (parent) strain with CXCL10 or a C-terminal truncated CXCL10 (CTTC) affected peptidoglycan processing and/or incorporation of precursors into the cell wall. B. anthracis ΔftsX or ftsE(K123A/D481N) mutant strains, which lacked a functional FtsE/X complex, exhibited little to no evidence of disruption in peptidoglycan processing by either CXCL10 or CTTC. Additional studies demonstrated that the B. anthracis parent strain exhibited a statistically significant increase in peptidoglycan release in the presence of either CXCL10 or CTTC. While B. anthracis ΔftsX strain showed increased peptidoglycan release in the presence of CXCL10, no increase was observed with CTTC, suggesting that the FtsE/X-independent pathway was responsible for the activity observed with CXCL10. These results indicate that FtsE/X-dependent killing of vegetative cells of B. anthracis results from a loss of cell wall integrity due to disruption of peptidoglycan processing and suggest that FtsE/X may be an important antimicrobial target to study in the search for alternative microbial therapeutics.